2022
DOI: 10.1177/17588359211068737
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRI (folinic acid, fluorouracil, and irinotecan) increases not efficacy but toxicity compared with single-agent irinotecan as a second-line treatment in metastatic colorectal cancer patients: a randomized clinical trial

Abstract: Background: FOLFIRI [irinotecan, folinic acid (CF), and fluorouracil] is considered a standard second-line chemotherapy regimen for patients with metastatic colorectal cancer (mCRC) who failed first-line XELOX/FOLFOX regimens. However, it remains unknown whether fluorouracil is still necessary in this case. This trial was designed to test the superiority of FOLFIRI over single-agent irinotecan as a second-line treatment for patients with mCRC. Methods: This randomized clinical trial was conducted in five hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…and the two promote each other's deterioration ( 26 , 27 ). Although chemotherapeutic drugs, such as 5-FU, CPT-11 and L-OHP, can induce intestinal injury ( 28 ), studies have yet to compare the differences between the intestinal injury degree and gut microbiota disorder pattern among them, which form the FOLFIRI (folinic acid, 5-FU, and CPT-11) and FOLFOX colorectal cancer chemotherapy regimens ( 29 ). Our study excluded the effects of different operators, seasonal climates, batches of mice, and mice from different environments, which allowed us to obtain accurate results for 5-FU-, CPT-11-, L-OHP-, and CF-induced intestinal injury and gut microbiota disorder in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…and the two promote each other's deterioration ( 26 , 27 ). Although chemotherapeutic drugs, such as 5-FU, CPT-11 and L-OHP, can induce intestinal injury ( 28 ), studies have yet to compare the differences between the intestinal injury degree and gut microbiota disorder pattern among them, which form the FOLFIRI (folinic acid, 5-FU, and CPT-11) and FOLFOX colorectal cancer chemotherapy regimens ( 29 ). Our study excluded the effects of different operators, seasonal climates, batches of mice, and mice from different environments, which allowed us to obtain accurate results for 5-FU-, CPT-11-, L-OHP-, and CF-induced intestinal injury and gut microbiota disorder in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown that chemotherapy drugs, such as 5-FU, CPT-11 and L-OHP, can induce intestinal injury (26), none have compared the differences between the intestinal injury degree and gut microbiota disorder pattern among them, which form the FOLFIRI and FOLFOX for colorectal cancer chemotherapy regimens (27). Our study excluded the effects of different operators, seasonal climates, batches of mice, and mice from different environments, which allowed us to obtain accurate results for 5-FU-, CPT-11-, L-OHP-, and CF-induced intestinal injury and gut microbiota disorder in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, both regimens are considered first-line therapy for cancer treatment. Several studies have been conducted to assess the effects of these combinations, and they have demonstrated that they are equally effective, with certain variations in median survival rates [ 1 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The usage of these schemes is defined by several factors such as geographical regions, patient genetics, individual response rate, oncologist’s preference, and socio-economic factors.…”
Section: Clinical Use Of Irinotecanmentioning
confidence: 99%